Scientific visualisation and the exploratory analysis of area data. - Wise, S.; Haining, Robert P.; Signoretta, P. (Environment & Planning A, 1999)
The writers discuss scientific visualization and the exploratory analysis of area data, paying particular attention to the growing number of software packages that provide visualization methods to support exploratory spatial data analysis (ESDA). The data in the exploratory analysis of nonspatial data are often thought to consist of both rough and smooth elements, so it can be argued that a software system for ESDA should have facilities for exploring the rough and smooth elements of both the spatial and nonspatial elements of the data. There is a need to examine the effectiveness of various visualization techniques in encouraging and supporting the exploratory analysis of spatial data.